Present, Past, and Future of Lean Six Sigma Applications: From Evolution to the Era of Artificial Intelligence - Singh, Alok B.; Gaurav, Gaurav; Sarkar, Prabir; Dangayach, Govind Sharan; Meena, Makkhan Lal (Recent Patents on Engineering, 2024)
Background: Lean Six Sigma is a fact-based, data-driven approach that avoids mistakes to improve quality and efficiency. Artificial intelligence (AI) is now evident in lean six sigma applications. AI waste elimination solutions can eliminate large amounts of waste that LSS could not. In lean six sigma, six sigma tackles process variance, whereas lean reduces waste to improve process quality and efficiency. Objective: To describe new pieces, trends, and the adoption and implementation of new technologies like AI by examining the current literature across multiple aspects for a more instructive and piquant viewpoint. Methods: This study is a combination of systematic and bibliometric review, where the systematic review was based on a class framework by selecting 97 articles from reputed journal databases, and the bibliometric review was conducted using a VOS viewer and web of science database for a period of 15 years (2007-2022). Results: By describing LSS's historical evolution, major concerns, prevalent research approaches, and application areas, the study helps practitioners and academics understand its present state for robust research. AI and other cutting-edge technologies help discover non-value-added operations that are difficult to recognize manually. Conclusion: This study has revealed the critical success factors for deploying LSS in numerous businesses. The motivations, barriers, and limits in the direction of the application of LSS are also discussed. The research trends in implementing modern technologies like AI showed a green wave. Future research may emphasize and dominate LSS implementation issues with modern technologies like AI.
Keywords: bibliometric analysis